Analisis Validitas dan Reliabilitas Soal Uraian Berbasis Google Form Dalam Menilai Kreativitas Ilmiah Siswa SMA - Simbolon, Elisabeth Endang Permata; Lingga, Loni Ignasia; Gomes, Margareth Jacoba Da; Jannah, Miftahul; Batubara, Rizki Salsabila; Mihardi, Satria; Bunawan, Wawan (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the validity and reliability of Google Form-based descriptive questions in assessing the scientific creativity of high school science students. Scientific creativity is an essential skill in science learning that includes flexibility of thinking, originality of ideas and elaboration in developing concepts and solving problems. By increasing the use of digital technology in learning evaluation, Google form becomes one of the platforms that offers convenience in compiling questions, collecting data in real-time and analyzing results systematically. This study uses a quantitative descriptive method by testing the validity and reliability of the descriptive question instrument through statistical analysis. The results of this study indicate that the Google Form-based assessment instrument has high validity with an average correlation value above 0.5 and good reliability with a consistency level above 0.7. In addition, this instrument is able to measure students' scientific creativity in answering questions based on three main indicators, namely flexibility, originality, and elaboration. This study shows that Google form can be used as a valid and reliable evaluation tool in assessing the scientific creativity of high school science students, but collaboration with other assessment methods is still needed to optimize the measurement of aspects of idea exploration and problem solving in more depth.